Pengaruh Kadar Dan Ukuran Selulosa Berbasis Batang Pisang Terhadap Sifat Dan Morfologi Bioplastik Berbahan Pati Umbi Talas - Roy Marthin Panjaitan; Irdoni Irdoni; Bahruddin Bahruddin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Plastic waste is one of environmental problem especially in Indonesia. Conventional plastic is made from synthetic polymer that is made by petroleum which hard to recycle or break down by microorganism. Bioplastic is the answer of this problem. Starch is kind of natural polymer that can be used for bioplastic production because the sources overflow, renewable and ready degradable. However, starch have a bad mechanical characteristic. Cellulose as the strengthened has been proved to overcome the lack of starch. This research is aim to analyze the effect of composition and size of cellulose particle to get the best combination of bioplastic mechanical characteristic and morphology. Bioplastic was made by casting method where the taro’s starch, glycerol and cellulose are mixed. This research take variable on addition level of cellulose 6, 9, 12, 15%wt with cellulose fiber sizes of 100, 150 and 200 mesh. The composition with a good characteristic was 15%wt cellulose with the size 150 mesh with strength 7,595 MPa, elongation 11,379%, modulus young 66,465 MPa, water uptake 37,50%, and biodegradation is about 36,11% in one week.Keyword : bioplastic, casting, cellulose, glycerol, starch